A Scoping Review of Tailored Self-management Interventions among Adults with Mobility Impairing Neurological and Musculoskeletal Conditions - Plow, Matthew; Mangal, Sabrina; Geither, Kathryn; Golding, Meghan (Frontiers in Public Health, 2016)
A critical public health objective is to optimize and disseminate self-management interventions for the 56.7 million adults living with chronic disabling conditions in the United States. A possible strategy to optimize the effectiveness of self-management interventions is to understand how best to tailor self-management interventions to the needs and circumstances of each participant. Thus, the purpose of this scoping review was to describe randomized controlled trials (RCTs) of tailored self-management interventions in adults with neurological and musculoskeletal conditions that characteristically result in mobility impairments. The 13 RCTs included in the scoping review typically compared tailored interventions to non-tailored interventions or usual care among adults with chronic pain, stroke, and/or arthritis. The tailored interventions were diverse in their delivery formats, dosing, behavior change techniques, and tailoring methodology. We identified 13 personal characteristics (e.g., preferences and theoretical constructs) and 4 types of assessment formats (i.e., oral history, self-report questionnaires, provider-reported assessments, and medical records) that were used to tailor the self-management interventions. It was common to tailor intervention content using self-report questionnaires that assessed personal characteristics pertaining to impairments and preferences. Content was matched to personal characteristics using clinical judgment or computer algorithms. However, few studies adequately described the decision rules for matching content. To advance the science of tailoring self-management interventions, we recommend conducting comparative effectiveness research and further developing a taxonomy to standardize descriptions of tailoring. We discuss the opportunities that are now coalescing to optimize tailored self-management. We also provide examples of how to merge concepts from the self-management literature with conceptual frameworks of tailoring from the health communication literature.